Russo-Chinese energy relations : politics in command - Blank, Stephen, 1950- (Global market briefings., 2006)
This report makes the point that in both Russia and China it is politics - and not market or commercial considerations - that largely drive energy relationships with each other and the outside world. For both countries, energy and energy security is regarded as a strategic asset and/or objective that are at risk from outside forces. Moreover, both countries are taking a statist - in Russia even patrimonial - approach to energy issues. Therefore cooperation between Russia and China will be difficult even though Russia wants to sell and China wants to buy. The conditions that each state has.